Analysis of swim turning, underwater gliding and stroke resumption phases in top division swimmers using a wearable inertial sensor device - Vannozzi, G.; Donati, M.; Gatta, G.; Cappozzo, A. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Improving swimming performance is a difficult task especially for élite athletes. A possibility is to investigate how optimising the timing of turning, underwater gliding and stroke resumption phases (Lyttle et al, 1999) by studying the relevant kinematics. Common video analysis is often inadequate to investigate motor tasks such as the swim turning. Swimming research recently started to include wearable accelerometers in their experimental setups (Slawson et al, 2008). This work aimed at describing the mentioned phases in top division swimmers using a wearable inertial device composed of a triaxial accelerometer and gyroscope. METHODS: Eight élite swimmers (4M, 4F) volunteered to participate in the study; they were part of a top division Italian team and were selected so as to cover all the four styles. A wearable inertial device (Sensorize, Italy) was used to measure 3D accelerations and angular velocities. The device was positioned on the lower trunk and a 50m trial at the maximum velocity was executed. Only angular velocities L, S and V about the three axes of the device frame of reference (lateral, L; sagittal, S, vertical, V) were post-processed. Phase durations, angular velocity peaks, stroke rate "sr" and the ratio "r" between gliding and stroke duration were analysed. RESULTS: Highest L (565 deg/s) was found in freestyle, highest V (354 deg/s) in backstroke flip-turn. Highest S (330 deg/s and 260 deg/s), conversely, were found in both breaststroke and butterfly. The sign of the rotation depended upon the turning technique. Sr was 62±3 and 54±6 for M and F; both sr and r lowered in the last lap. Consistently, higher r were found for backstroke (0.7±0.1), the lower for freestyle (0.3±0.1). DISCUSSION: The feasibility to use inertial sensors to characterise turning, gliding and stroke resumption in swimming was verified. Strength points of the approach are: simple description of the turning kinematics; possibility to extract performance-related parameters; simplicity of use for the operator; the minimal encumber for the athlete. Future steps are the inclusion of further athletes, the definition of further parameters, eventually specific for each swimming styles.